2013
DOI: 10.1002/met.1389
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a statistically initialized fuzzy logic scheme for classifying the severity of convective storms in Finland

Abstract: This paper proposes a method for classifying the severity of individual convective storms with real-time weather radar and lightning location data. The algorithm is based on a statistically initialized fuzzy logic model with human-oriented linguistic inference rules. When combined with an object-oriented convective storm tracking algorithm, the severity classification uses the past severity values in addition to the current state of the storm. Furthermore, the proposed method can be customized to correspond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 59 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The applied reflectivity thresholds vary typically in the range 30-45 dBZ (e.g. Seroka et al, 2012;Goudenhoofdt and Delobbe, 2013;Rossi et al, 2014). Higher threshold values are better for detecting individual convective cores, while lower thresholds allow larger scale storm systems, which can include multiple convective cores, to be identified.…”
Section: Storm Cell and Other Radar Based Storm Characteristic Definimentioning
confidence: 99%
“…The applied reflectivity thresholds vary typically in the range 30-45 dBZ (e.g. Seroka et al, 2012;Goudenhoofdt and Delobbe, 2013;Rossi et al, 2014). Higher threshold values are better for detecting individual convective cores, while lower thresholds allow larger scale storm systems, which can include multiple convective cores, to be identified.…”
Section: Storm Cell and Other Radar Based Storm Characteristic Definimentioning
confidence: 99%
“…Their results showed that the event‐based estimation approach yields better forecasts. Other useful methods for precipitation analysis are Tropical rainfall measuring mission (TRMM) Multi‐satellite Precipitation Analysis (Pombo et al , ; Dasari and Salgado ), fuzzy technique (Yu et al, ; Hasan et al, ; Kisi and Shiri, ; Kisi and Shiri, ; Rossi et al, ), radar data method (Burlando et al , ; Korsholm et al , ) and spatial and temporal variability analyses (http://www.tandfonline.com/action/doSearch?action=runSearch&type=advanced&searchType=journal&result=true&prevSearch=%2Bauthorsfield%3A%28Wagesho%2C+N%29 et al, ; Foresti and Seed, ; Kim and Lee, ; Wu et al, ). On the other hand, although there are many methods to model hydrological phenomena (Valipour and Eslamian, ; Valipour, , , , , , ; Mahdizadeh Khasraghi et al, ; Rahimi et al, ; Valipour et al, , ), artificial neural network (ANN) is a powerful model for agricultural and forest meteorology analysis.…”
Section: Introductionmentioning
confidence: 99%